Teacher’s Perspectives of Integrated Therapy Service Deliveries: A Case Study - Pingale, Vidya; Fletcher, Tina S. (Journal of the American Academy of Special Education Professionals, 2024)
This qualitative case study explored an elementary school teacher’s perspectives of integrated therapy service deliveries (ITSD) using a semi-structured interview. An inductive emergent sampling was used to select the participant from an urban school district. A grounded theory approach was used to analyze the data and understand the teacher’s perspectives of ITSD within their personal, social, cultural, and environmental contexts. Analysis revealed teacher’s perspectives of ITSD, dynamic trajectories of ITSD, and interdependence as themes. The teacher’s perspectives of ITSD were influenced by the impact of ITSD on the classroom and the teacher’s sense of control in the classroom. Trajectories of ITSD were shaped by variations in the implementation process, presence of catalysts, and integration into the classroom. Interdependence was seen between trajectories of ITSD and teacher’s perspectives. Overall, the teacher viewed ITSD as beneficial, and their perspectives were crucial for the success of ITSD.